2005
DOI: 10.1126/science.1107008
|View full text |Cite
|
Sign up to set email alerts
|

Extensive DNA Inversions in the B. fragilis Genome Control Variable Gene Expression

Abstract: The obligately anaerobic bacterium Bacteroides fragilis, an opportunistic pathogen and inhabitant of the normal human colonic microbiota, exhibits considerable within-strain phase and antigenic variation of surface components. The complete genome sequence has revealed an unusual breadth (in number and in effect) of DNA inversion events that potentially control expression of many different components, including surface and secreted components, regulatory molecules, and restriction-modification proteins. Inverti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
205
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(209 citation statements)
references
References 22 publications
4
205
0
Order By: Relevance
“…There were genes for Hly type I secretion systems, which are similar to the hemolysin type I secretion system HlyDb from E. coli (288), or the type II general secretion pathway (54). The large quantity of enzyme-containing outer membrane vesicles produced by B. fragilis (185) suggests that this may be an important export pathway (54). The Bacteroides genome also contains large numbers of gene homologs of a variety of efflux pumps systems whose export functions have not yet been defined.…”
Section: Cell Surface Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…There were genes for Hly type I secretion systems, which are similar to the hemolysin type I secretion system HlyDb from E. coli (288), or the type II general secretion pathway (54). The large quantity of enzyme-containing outer membrane vesicles produced by B. fragilis (185) suggests that this may be an important export pathway (54). The Bacteroides genome also contains large numbers of gene homologs of a variety of efflux pumps systems whose export functions have not yet been defined.…”
Section: Cell Surface Structuresmentioning
confidence: 99%
“…The genomic studies of B. fragilis did not show evidence of type III, IV, autotransporter, or two-partner secretion systems. There were genes for Hly type I secretion systems, which are similar to the hemolysin type I secretion system HlyDb from E. coli (288), or the type II general secretion pathway (54). The large quantity of enzyme-containing outer membrane vesicles produced by B. fragilis (185) suggests that this may be an important export pathway (54).…”
Section: Cell Surface Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic bacteria use the phase variability of gene expression to evade the host immune system. Based on sequence analysis and biochemical evidence, many type I and III enzymes of Bacteroides fragilis as well as Haemophilus, Helicobacter, Mycoplasma, and Neisseria species were found to be potentially phase variable (176)(177)(178)(179)(180)(181). The biological significance of R-M systems that exhibit phase variability is not completely understood.…”
Section: Functions Of Phase-variable R-m Systemsmentioning
confidence: 99%
“…(iii) Whole-genome sequencing of B. fragilis revealed that many R-M systems of bacteria undergo inversions (176). It has been proposed that phase variation in these bacteria increases the diversity of R-M systems, generating up to eight different recognition subunits (176 (180,181).…”
Section: Functions Of Phase-variable R-m Systemsmentioning
confidence: 99%